Respuesta :

Answer:

Step-by-step explanation:

To find the derivative of inverse hyperbolic function sinh-'(x),

Let [tex]y =sinh-'(x),\\x = sinhy[/tex]

This is an implicit function.  Now differentiate both the sides.

[tex]1=coshy \frac{dy}{dx} \\\frac{dy}{dx}=\frac{1}{coshy}[/tex]

In hyperbolic functions we have relation as

[tex]cosh^2 x- sinh^2 x =1\\coshy = \sqrt{1+sinh^2 y} =\sqrt{1+x^2}[/tex]

Hence derivative = [tex]\frac{1}{\sqrt{1+x^2} }[/tex]

ACCESS MORE
EDU ACCESS
Universidad de Mexico